Satellites Missions and Technologies for Geosciences - Demyanov, Vladislav; Becedas, Jonathan (IntechOpen, 2020)
Being a vital modern technology, satellite systems for navigation, telecommunication, and geosciences have developed rapidly in the last 25 years. Modern satellite technologies have become a base of our civilization and support our day-to-day activity in both practice and geosciences. This book is devoted to GNSS-remote sensing for ionosphere research, modeling and mitigation techniques to diminish the ionosphere and multipath impacts on GNSS, and survey of the modern satellite missions and technologies. We hope that the experts' opinions presented in the book will be interesting for the research community and students in the area of satellites and space missions as well as in engineering and geoscience research.